2019
DOI: 10.3390/ma12172716
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Rectangular-Sectional Steel Tubular Columns Filled with High-Strength Steel Fiber Reinforced Concrete Under Axial Compression

Abstract: This paper studies the effect of high-strength steel fiber reinforced concrete (SFRC) on the axial compression behavior of rectangular-sectional SFRC-filled steel tube columns. The purpose is to improve the integrated bearing capacity of these composite columns. Nine rectangular-sectional SFRC-filled steel tube columns and one normal concrete-filled steel tube column were designed and tested under axial loading to failure. The compressive strength of concrete, the volume fraction of steel fiber, the type of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…To overcome the casting difficulty of concrete in structural members and joints with complex shapes and dense reinforcements, and to reduce the environmental pollution of vibration noise, a high-performance self-compacting steel fiber reinforced concrete (SFRC) becomes more and more applicable in engineering structures [1][2][3][4]. Self-compacting SFRC not only realizes the self-compacting performance with high passing and filling workability without segregation and bleeding, but also overcomes the brittleness of self-compacting concrete (SCC) by using steel fibers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the casting difficulty of concrete in structural members and joints with complex shapes and dense reinforcements, and to reduce the environmental pollution of vibration noise, a high-performance self-compacting steel fiber reinforced concrete (SFRC) becomes more and more applicable in engineering structures [1][2][3][4]. Self-compacting SFRC not only realizes the self-compacting performance with high passing and filling workability without segregation and bleeding, but also overcomes the brittleness of self-compacting concrete (SCC) by using steel fibers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This could significantly increase the bearing capacity of the structure [ 4 , 5 , 6 , 7 , 8 ]. Previous studies [ 9 , 10 , 11 , 12 , 13 ] also showed that the CFST column has high flexibility, high energy absorption, and high reliability when used for earthquake-resistant buildings. Moreover, it is able to reduce the impact on the environment by eliminating formwork, and the steel pipes could be reused, or using high-strength concrete with recycled materials.…”
Section: Introductionmentioning
confidence: 99%
“…With such bearing characteristics, the cross-section of the CFST column is usually in the form of circle, square, rectangle, or ellipse [ 13 ]. For load-bearing components in two uneven directions, the cross-section of CFST is usually chosen in the form of rectangular or elliptical shapes [ 8 , 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, concrete filled steel tubes (CFSTs) have been widely used in the construction of modern buildings and bridges [4], even in high seismic risk areas [5][6][7][8][9][10]. This increase in use is because of the significant advantages that the CFST column system offers over conventional steel or reinforced concrete systems, such as high axial load capacity [4], good plasticity and toughness [6], techniques; different ANN-based modeling methods have been used by scientists in many construction engineering applications [42]. Sanad et al [43] used ANN to estimate the reinforced concrete deep beams ultimate shear strength.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the square and rectangular CFST columns have the advantage of easy connection and reliable work with other structural members such as beams, walls, and panels [20]. Compared with square CFST columns, rectangular columns have irregular bending stiffness along different axes, so this type of column is suitable for the mechanical behavior of members including arch ribs, pillars, abutments, and piers, and other structural members under load actions vary greatly from vertical to horizontal [6]. Because the scope of application of rectangular CFST columns is quite wide and this column is mainly subjected to compression, the main purpose of the paper is to analyze and evaluate the ultimate bearing capacity of rectangular columns.In recent decades, the regulations for calculating the CFST column type have been proposed in design standards such as AISC-LRFD [21], ACI 318-05 [22], Japan Institute of Architecture [17], European Code EC 4, British Standard BS 5400 [23], and Australian Standard AS-5100.6 [24].…”
mentioning
confidence: 99%